Optimasi Perbandingan Monomer Fungsional dan Pengikat Silang (Crosslinker) untuk Sintesis MIPs-Auramine Menggunakan Metode Fotopolimerisasi - Aulia Safrika; Alizar Ulianas (MASALIQ, 2026)
The successful synthesis of molecularly imprinted polymers (MIPs) is highly determined by the selection and ratio of functional monomers and cross-linkers, as these components directly affect adsorption capacity. The use of inappropriate types or ratios of functional monomers and cross-linkers can reduce adsorption capacity, either because quantities that are too low produce insufficiently stable polymers or because excessive quantities lead to non-specific interactions and overly dense polymer structures. This study aimed to determine the optimum ratio between the functional monomer and cross-linker for synthesizing MIPs-auramine. Methacrylic acid (MAA) was used as the functional monomer and ethylene glycol dimethacrylate (EGDMA) as the cross-linker, selected for their good stability, with a photopolymerization method that enables rapid MIPs synthesis and the formation of relatively uniform polymer structures. The study employed a quantitative approach with varied amounts of MAA and EGDMA, which were evaluated based on their adsorption capacity toward auramine dye. Data were collected using a UV-Vis spectrophotometer to determine the concentration of adsorbed auramine. The experimental results showed that the optimum MAA–EGDMA ratio for MIPs synthesis was 0.02 mol : 0.005 mol, with adsorption capacities of 0.580 mg/g and 0.640 mg/g, respectively. This optimum ratio was subsequently used to synthesize MIPs-auramine that effectively adsorb auramine dye, while also contributing to a better understanding of the relationship between monomer–cross-linker composition and the resulting polymer characteristics. The practical implications of this study indicate the potential application of MIPs-auramine in the selective detection and removal of auramine on an industrial scale.